(untitled) (Živi jezici: Journal for Foreign Languages and Literatures, 2025)
Mastering technical vocabulary is one of the primary goals of teaching a foreign language for specific purposes, making the identification and use of appropriate dictionaries as reference materials invaluable in the teaching and learning process. This paper aims to present existing monolingual and bilingual dictionaries and glossaries in the field of special education and rehabilitation and to highlight their advantages and disadvantages in accordance with the needs of first-year students at the Faculty of Special Education and Rehabilitation, University of Belgrade. Additionally, the paper points to the need for the creation of a modern, adequate, and accessible dictionary in this field, which would meet the needs of the target group of students and be used as an additional teaching tool within the English for Specific Purposes university course.